Grundsätzliche Überlegungen zu einer Entkopplung der Direktzahlungen in der EU; Basic Considerations of a Decoupling of Direct Payments within the EU - Gunnar Breustedt (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– This paper analyses theoretically the consequences of decoupling and argues for a wider discussion among agricultural economists and the public. Quantitative work on forecasting the consequences seems to be problematic in general. We ask, if the allocation of land will change that dramatically, in particular, we wonder whether set-aside will increase that much as some research and statements argue if direct payments are abolished or decoupled from land use. Taking into account economies of scale that can be realised because of faster change in the farming structure, adapted behaviour of farmers due to dramatic changes in the subsidisation scheme, technological progress, and price changes of factors and products in farmers' benefit we conclude that most quantitative forecasts probably overestimate the changes in land allocation. Social objectives that may be incorporated with agricultural land use are analysed as well as the efficiency of direct payments to achieve these objectives. Distributional effects of income are taken into consideration, too. We recommend that politicians should decide as soon as possible to abolish or adirect payments stepwise over some years. Farmers should be aware of an end for the direct payments and should keep high flexibility to adapt to the future as easy as possible. Therefore, they should avoid investments with a high portion of sunk costs and they should analyse their capital use, especially on marginal land. Further on, they should try to reduce costs by increasing the size of farms and acres.
Keywords: 330; Agrarsubvention; EU-Agrarpolitik; Agrarreform; Wirkungsanalyse; Neue klassische Makroökonomik; Agrarökonomik